Photochemically Produced Singlet Oxygen: Applications and Perspectives. Issue 7 (11th June 2018) - Pibiri, Ivana; Buscemi, Silvestre; Palumbo Piccionello, Antonio; Pace, Andrea
Abstract: This Review aims to provide early stage researchers with an updated guide to applications of photochemically produced singlet oxygen and, at the same time, widen the experienced researcher's perspectives in a holistic approach to singlet oxygen chemistry. Without being exhaustive, literature between 2010 and early 2018 has been surveyed by focusing on a critical evaluation of new knowledge and applications. After an introductory section concerning singlet oxygen production, detection, and interactions with biological systems, subsequent sections describe current applications of singlet‐oxygen‐enabled technology. Besides strictly chemical synthesis applications, attention has been given to the usage of singlet oxygen in photochemically assisted therapies as well as in environmental remediation. Additionally, the potential of expanding singlet oxygen chemistry to unexplored fields has been discussed. Abstract : What's 1 O2 got to do with it? This Review provides an updated guide for photochemists to applications of photochemically produced singlet oxygen. An overview of singlet oxygen production, detection and interactions with biological systems is provided and applications in synthesis, phototherapy and environmental remediation are described.